2010
DOI: 10.3354/meps08824
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of shifts in spawning seasonality and size at maturation on the population growth of mantis shrimp in Tokyo Bay

Abstract: The spawning season of mantis shrimp Oratosquilla oratoria (Stomatopoda) in Tokyo Bay has changed from being unimodal (spring only) to bimodal (spring and summer).This shift in the pattern of spawning arose because reproductive maturation began to occur in smaller females, which presumably spawn in summer, and because the proportion of smaller mature females increased. Currently, recruitment appears to depend entirely on the summer cohort because of significantly lower juvenile survival in the spring cohort. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…According to Ahyong et al (2008), mantis shrimp reach the maturity stage at a length of 10-30 cm. On the other hand, Nakajima et al (2010) reported that for Oratosquila oratoria, maturity started from 10 cm. The sex ratio of the two species of mantis shrimp differed, which may be related to differences in the behavioral pattern of spawning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ahyong et al (2008), mantis shrimp reach the maturity stage at a length of 10-30 cm. On the other hand, Nakajima et al (2010) reported that for Oratosquila oratoria, maturity started from 10 cm. The sex ratio of the two species of mantis shrimp differed, which may be related to differences in the behavioral pattern of spawning.…”
Section: Discussionmentioning
confidence: 99%
“…This result was related to recruitment periods in the preceding months. Nakajima et al (2010) reported that in the period of May-July the lengths of Oratosquilla mantis shrimps were < 10 cm in length, while in August the Oratosquilla were bigger (i.e. >10 cm in length).…”
Section: Discussionmentioning
confidence: 99%